Mengelola Konsep Dasar Siaran Radio, Televisi, dan Multimedia (Internet) Bermuatan Dakwah - Anugrah, Indah; Sara, Umi; Effendy, Erwan (MES Bogor, 2023)
Managing is to regulate, control, manage and regulate. Managing the basic concepts of radio, television and multimedia that contain da'wah means how we as da'i, producers or preachers regulate the concept of da'wah through this media in order to achieve the goal of da'wah. With this information technology can facilitate all activities. In the past, when you wanted to convey a message to someone who was far away, you still used a written letter, even through the post office to send it. This research is a descriptive study by describing and explaining how to manage the basic concepts of radio, television, and multimedia (internet) containing da'wah that has occurred from the past until now in Indonesia. Radio, television and internet are media that developed from the era of era that can be used as a medium of da'wah. So we as Muslims, preachers and television producers must be good at managing this media as well as possible so that the da'wah delivered is right on target. Making this media as a developing that can convey its da'wah. Whatever method of da'wah that is carried out in the real world, it has been able to be displayed in cyberspace precisely. The challenge for the da'i in using the media is how the da'i maintains this media so that it does not become extinct or this media persists in delivering da'wah and is able to develop and convey da'wah widely through this media. Therefore, da'wah in this global era must use modern information technology in conveying messages of Islamic teachings. This modern media information technology can be used in every condition and place, both in urban and rural areas. This can make it easier for the dai in conveying his da'wah to the da'wah targets. Keywords: manage,media, da’wah